2020
DOI: 10.1038/s41598-020-60096-1
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF Val66Met polymorphism affects negative memory bias in civilian women with PTSD

Abstract: Memory abnormalities are considered a core feature of posttraumatic stress disorder (PTSD). Studies attempting to quantify such memory dysfunction in PTSD have reported that individuals with this disorder exhibit selective memory bias toward negative material. The low expression Met allele of brainderived neurotrophic factor (BDNF) Val66Met polymorphism has been associated with the aetiology of PTSD and with memory abnormalities. It is therefore possible that the BDNF Val66Met polymorphism can moderate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Finally, 16 studies with 1,739 patients and 3,630 controls met the inclusion and exclusion criteria (Bruenig et al., 2016; Dai et al., 2017; Dretsch et al., 2016; Guo et al., 2018, 2019; Heon‐Jeong et al., 2006; Hori et al., 2020; Jin et al., 2019; Li et al., 2016; Lyoo et al., 2011; Pivac et al., 2012; Qi et al., 2020; Valente et al., 2011; Young et al., 2018; Zhang et al., 2006, 2014). There were four studies in Caucasian populations (Bruenig et al., 2016; Pivac et al., 2012; Young et al., 2018; Zhang et al., 2006), nine studies in Asian populations (Dai et al., 2017; Guo et al., 2018, 2019; Heon‐Jeong et al., 2006; Hori et al., 2020; Jin et al., 2019; Li et al., 2016; Lyoo et al., 2011; Qi et al., 2020), and three studies in mixed populations (Dretsch et al., 2016; Valente et al., 2011; Zhang et al., 2014). Five studies used the polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) method, while the rest used real‐time PCR, TaqMan, SnaPShot, Sequencer platform, and Illumina methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 16 studies with 1,739 patients and 3,630 controls met the inclusion and exclusion criteria (Bruenig et al., 2016; Dai et al., 2017; Dretsch et al., 2016; Guo et al., 2018, 2019; Heon‐Jeong et al., 2006; Hori et al., 2020; Jin et al., 2019; Li et al., 2016; Lyoo et al., 2011; Pivac et al., 2012; Qi et al., 2020; Valente et al., 2011; Young et al., 2018; Zhang et al., 2006, 2014). There were four studies in Caucasian populations (Bruenig et al., 2016; Pivac et al., 2012; Young et al., 2018; Zhang et al., 2006), nine studies in Asian populations (Dai et al., 2017; Guo et al., 2018, 2019; Heon‐Jeong et al., 2006; Hori et al., 2020; Jin et al., 2019; Li et al., 2016; Lyoo et al., 2011; Qi et al., 2020), and three studies in mixed populations (Dretsch et al., 2016; Valente et al., 2011; Zhang et al., 2014). Five studies used the polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) method, while the rest used real‐time PCR, TaqMan, SnaPShot, Sequencer platform, and Illumina methods.…”
Section: Resultsmentioning
confidence: 99%
“…In knock‐in mice, extinction learning was impaired in Met allele carriers compared to non‐Met allele carriers (Soliman et al., 2010); there was a similar finding in patients with PTSD with the Met allele when compared to those with the Val allele (Felmingham et al., 2018). A human study by Horri et al revealed that PTSD patients with the Met allele had significantly worse memory performance than controls, indicating that the rs6265 polymorphism could be involved more in core memory abnormalities than general memory dysfunction in PTSD (Hori et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Second, as we only included female participants, it is unknown whether the present findings might be specific to women or common to both sexes. The main reason for the focus on female patients was that this study built on our previous studies of childhood maltreatment, cognitive function, memory bias, inflammation, and the BDNF Val66Met polymorphism in women with PTSD 61,[92][93][94] . In addition, it was necessary to consider potential sex differences in this study, given the evidence for differential psychobiological impacts of childhood maltreatment between sexes 95 and for sexually dimorphic effects of the BDNF Val66Met polymorphism 49 .…”
Section: Discussionmentioning
confidence: 99%
“…This SNP has also been associated with attention bias 56 , 57 and circulating inflammatory markers 58 , 59 . Furthermore, this SNP has been associated with exaggerated expression of memories with negative emotional valence in both mice 60 and human PTSD patients 61 . These findings together suggest that the BDNF Val66Met polymorphism may affect attention bias and ABV by interacting with childhood maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the A allele was associated with greater severity of lifetime and current PTSD symptoms in a large number of European American U.S. military veterans [ 53 ]. The A carriers had reduced competence in judging their spatial processing of navigation performance [ 54 ], negative memory bias [ 55 ], higher re-experiencing symptoms [ 53 ], elevated hyperarousal vulnerability, and increased startle scores [ 56 ], compared to GG genotype carriers. In our previous study that included a smaller number of war veterans with or without PTSD, we have detected significant association between cognition (visual-spatial perception and short and long-term visual memory function) determined using the Rey-Osterrieth Complex Figure (ROCF) test and BDNF rs6265 in war veterans with PTSD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%